Optimizing computational resource management for the scientific gateways ecosystems based on the service‐oriented paradigm. (26th February 2020) - Martins de Oliveira, Edvard; Estrella, Júlio Cézar; Botazzo Delbem, Alexandre Claudio; Souza Pardo, Mário Henrique; Guzzo da Costa, Fausto; Defelicibus, Alexandre; Reiff‐Marganiec, Stephan
Summary: Science Gateways provide portals for experiments execution, regardless of the users' computational background. Nowadays its construction and performance need enhancement in terms of resource provision and task scheduling. We present the Modular Distributed Architecture to support the Protein Structure Prediction (MDAPSP), a Service‐Oriented Architecture for management and construction of Science Gateways, with resource provisioning on a heterogeneous environment. The Decision Maker, central module of MDAPSP, defines the best computational environment according to experiment parameters. The proof of concept for MDAPSP is presented in WorkflowSim, with two novel schedulers. Our results demonstrate good Quality of Service (QoS), capable of correctly distributing the workload, fair response times, providing load balance, and overall system improvement. The study case relies on PSP algorithms and the Galaxy framework, with monitoring experiments to show the bottlenecks and critical aspects.